2020
DOI: 10.14715/cmb/2020.66.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Phytol anti-inflammatory activity: Pre-clinical assessment and possible mechanism of action elucidation

Abstract: Phytol (PHY) is an acyclic natural diterpene alcohol and a chlorophyll constituent that exhibits several pharmacological effects, such as anticancer, antioxidant, and antimicrobial. Here, we aimed to assess the PHY anti-inflammatory effect in vitro and in vivo, and to deepen knowledge on the possible mechanism of action. For this purpose, egg albumin (in vitro) test was performed by using acetyl salicylic acid (ASA) as a standard nonsteroidal anti-inflammatory drugs (NSAID). For in vivo test, male Wistar albin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…e biological activities of phytol and phytosterols can be attributed to antiinflammatory activities through reduction of leukocyte and neutrophil migration, IL-1β, IL-6, and TNF-α levels and oxidative stress, as well as antibacterial effects [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e biological activities of phytol and phytosterols can be attributed to antiinflammatory activities through reduction of leukocyte and neutrophil migration, IL-1β, IL-6, and TNF-α levels and oxidative stress, as well as antibacterial effects [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that squalene promotes remodelling and tissue repair response signals by inhibiting the nuclear factor-kappa B, inducible nitric oxide synthase, the production of proinflammatory cytokines, such as IL-1 β and TNF- α , and stimulation of anti-inflammatory cytokines IL-10 and IL-4 [ 46 , 47 ]. The biological activities of phytol and phytosterols can be attributed to anti-inflammatory activities through reduction of leukocyte and neutrophil migration, IL-1 β , IL-6, and TNF- α levels and oxidative stress, as well as antibacterial effects [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, D represents the adjacency matrix [10]. Graph convolution is similar to traditional convolution in that the calculation process of graph convolution is also a process of sampling first and then weighting and summing [11][12]. The sampling method of graph convolution is similar to traditional convolution.…”
Section: Deep Learningmentioning
confidence: 99%
“…1. Phytol is a diterpene used as precursor for vitamin K and is recognised for its antimicrobial, anticancer, ant-inflammatory, antidiuretic, hypocholesterolemic and antioxidant activities 33 . 3-Tetradecyn-1-ol is an alcoholic compound that has antibacterial effect 34 .…”
Section: Docking and Visualisation Of The Complexesmentioning
confidence: 99%